2011
DOI: 10.1590/s0104-11692011000100005
|View full text |Cite
|
Sign up to set email alerts
|

Risk classification in an emergency room: agreement level between a Brazilian institutional and the Manchester Protocol

Abstract: The aim of this study was to assess the level of agreement between an institutional protocol and the Manchester protocol for the risk assessment of patients attended in an emergency room of a public hospital in Belo Horizonte -MG -Brazil. This is a descriptive and comparative study, in which 382 patients' reports were evaluated and the risk was classified, using the institutional protocol and the Manchester protocol. Rates were calculated through weighted and unweighted kappa, in order to determine the level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
1
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 8 publications
2
60
1
11
Order By: Relevance
“…Similarly, other studies (3,(11)(12)14,18,20) have already shown an association between priority attributed by the MTS and severity levels (18,20) , risk of remaining hospitalized (11)(12)18,20) , length of hospital stay (18) , and risk of death (11)(12)18,20) . One of these studies (18) proved that the mean of number of days of hospital stay decreased in the same order of complexity of patient status ( red, orange, yellow, and green).…”
Section: Discussionsupporting
confidence: 53%
“…Similarly, other studies (3,(11)(12)14,18,20) have already shown an association between priority attributed by the MTS and severity levels (18,20) , risk of remaining hospitalized (11)(12)18,20) , length of hospital stay (18) , and risk of death (11)(12)18,20) . One of these studies (18) proved that the mean of number of days of hospital stay decreased in the same order of complexity of patient status ( red, orange, yellow, and green).…”
Section: Discussionsupporting
confidence: 53%
“…(1) A study carried out in Brazil compared the MTS with an institutional classification system showing that the former is more inclusive and increases the priority level of the classified patients. (8) In a study carried out in Portugal, the MTS was useful to distinguish patients who needed emergency care from the others. (9) Brazil and Portugal have similar health services; in both, the health system is controlled by the State, is ruled laws of the Federal Constitution and is under the responsibility of the Ministry of Health.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the system has been well adapted to the Brazilian reality, but that validation studies are needed because it is new technology in the implementation phase within the country. 8 Another Brazilian study established the predictive validity of the MTS deployed at the entrance door of an urgent service in Belo Horizonte, MG. This study also utilized the Therapeutic Intervention Scoring System -28 (TISS -28) to measure the severity of patients after 24 hours of admission to the ED.…”
Section: Introductionmentioning
confidence: 99%